Mechanisms of quinolone resistance in Salmonella spp. / Mecanismos de resistência às quinolonas em Salmonella spp. - Tereza Cristina Rocha Moreira de Oliveira (Semina: Ciências Agrárias, 2010)
Salmonellosis is a common and widespread zoonotic disease of humans and a frequent cause of foodborne disease. Treatment of severe and systemic salmonellosis is usually done with fluoroquinolones. In this review resistance mechanisms of Salmonella to quinolones are discussed. Single point mutations in the quinolone resistant determining region (QRDR) of the gyrA gene may be sufficient to generate high levels of resistance to non-fluorated quinolones and also may decrease the fluoroquinolones susceptibility. Other resistance mechanisms that should be considered are mutations in parC gene, the possibility of acquiring resistance through plasmidial transference and hyper-expression of efflux pumps. Fluoroquinolones resistance is still relatively uncommon in Salmonella compared to other species belonging to the Enterobacteriaceae family. However, the more careful use of fluoroquinolones in veterinary and human medicine is essential to decrease the selective pressure which can avoid the emergence and spread of resistant clones and consequently maintain the clinical efficacy of this group of antibiotics. A salmonelose é uma zoonose de importância mundial e uma das mais freqüentes doenças de origem alimentar. As fluoroquinolonas são a principal opção para o tratamento de salmoneloses graves ou sistêmicas. Esta revisão de literatura teve como objetivo apresentar os principais mecanismos envolvidos na resistência de Salmonella spp a estes antimicrobianos. Mutações de ponto na Região Determinante de Resistência à Quinolona (QRDR) do gene gyrA podem gerar altos níveis de resistência a quinolonas não-fluoradas, além de reduzir a suscetibilidade as fluoroquinolonas. Outros mecanismos de resistência que também precisam ser considerados são as mutações no gene parC, a possibilidade do envolvimento de plasmídios de resistência e o sistema de efluxo ativo. A resistência às fluoroquinolonas ainda é incomum em Salmonella spp., quando comparada a outros gêneros da família Enterobacteriaceae. No entanto, o uso criterioso de fluoroquinolonas na medicina humana e veterinária é essencial para reduzir a pressão seletiva e evitar a emergência e disseminação de clones resistentes, mantendo o espectro de ação e a eficácia clínica desta classe terapêutica.